Exogenous attention to fear: Differential behavioral and neural responses to snakes and spiders. (May 2017) - Soares, Sandra C.; Kessel, Dominique; Hernández-Lorca, María; García-Rubio, María J.; Rodrigues, Paulo; Gomes, Nuno; Carretié, Luis
Abstract: Research has consistently shown that threat stimuli automatically attract attention in order to activate the defensive response systems. Recent findings have provided evidence that snakes tuned the visual system of evolving primates for their astute detection, particularly under challenging perceptual conditions. The goal of the present study was to measure behavioral and electrophysiological indices of exogenous attention to snakes, compared with spiders – matched for rated fear levels but for which sources of natural selection are less well grounded, and to innocuous animals (birds), which were presented as distracters, while participants were engaged in a letter discrimination task. Duration of stimuli, consisting in a letter string and a concurrent distracter, was either presented for 180 or 360 ms to explore if the stimulus duration was a modulating effect of snakes in capturing attention. Results showed a specific early (P1) exogenous attention-related brain potential with maximal amplitude to snakes in both durations, which was followed by an enhanced late attention-related potential (LPP) showing enhanced amplitudes to spiders, particularly under the longer exposure durations. These results suggest that exogenous attention to different classes of threat stimuli follows a gradual process, with the most evolutionary-driven stimulus, i.e., snakes, being more efficient at attracting early exogenous attention, thus more dependent on bottom-up processes. Highlights: We measured behavioral and neural indices of attention to snakes and spiders. We used an exogneous attention task and manipulated stimulus duration. Results showed maximal amplitudes in P1 for snakes in both exposure durations. Enhanced LPP amplitudes in longer durations were observed for spiders. Reaction times and error rates showed significant correlations with LPP amplitudes.